2014
DOI: 10.1016/j.canlet.2014.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitization of tumor cells through endoplasmic reticulum stress induced by PEGylated nanogel containing gold nanoparticles

Abstract: High atomic number molecules, such as gold and platinum, are known to enhance the biological effect of X-irradiation. This study was aimed to determine the radiosensitizing potential of PEGylated nanogel containing gold nanoparticles (GNG) and the cellular mechanism involved. GNG pretreatment increased the levels of reproductive cell death and apoptosis induced by X-irradiation. GNG accumulated in cytoplasm and increased the expression of endoplasmic reticulum (ER) stress-related protein. GNG suppressed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 40 publications
(56 reference statements)
2
50
0
Order By: Relevance
“…[7][8][9] Nanoparticles can be retained in tumors through two independent mechanisms: passive targeting and active targeting. Passive targeting is based on the preferential accumulation of nanoparticles within tumor tissue by permeating the leaky angiogenic endothelium (enhanced permeability and retention effect), but specific tumor targeting is not possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] Nanoparticles can be retained in tumors through two independent mechanisms: passive targeting and active targeting. Passive targeting is based on the preferential accumulation of nanoparticles within tumor tissue by permeating the leaky angiogenic endothelium (enhanced permeability and retention effect), but specific tumor targeting is not possible.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Numerous studies have shown that GNPs can be used as effective radiosensitizers by enhancing the efficacy of physical radiation (RT) on tumor cells. [7][8][9] In published studies, kilovolt radiosensitization has been attributed to increased photon absorption in high-Z materials compared with soft tissue. Photoelectric absorption is more prominent at kilovolt energies than at megavolt energies, at which the Compton effects are dominant.…”
Section: Introductionmentioning
confidence: 99%
“…This study, however, gave more details on the relationship of sensitization activity not only with AuNP concentrations but also with the X-ray doses, offering more information in understanding the radiosensitization mechanism. Cell surviving curve was used to describe the relationship between the radiation dose and the proportion of cells that survive (40,41). Radiosensitization activity by AuNPs and the combination effects with DOX were confirmed by comparing the surviving curves in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Synthesis of nanoparticles of noble metals is of enormous importance due to their biomedical, pharmaceutical, optical, electronic and chemical properties [1][2][3][4][5][6][7][8][9]. Microbial interactions with metals have been explored for biotechnological application such as ore leaching and metal recovery [10][11][12].…”
Section: Introductionmentioning
confidence: 99%